Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.